2020
DOI: 10.48550/arxiv.2012.10289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HateXplain: A Benchmark Dataset for Explainable Hate Speech Detection

Abstract: Hate speech is a challenging issue plaguing the online social media. While better models for hate speech detection are continuously being developed, there is little research on the bias and interpretability aspects of hate speech. In this paper, we introduce HateXplain, the first benchmark hate speech dataset covering multiple aspects of the issue. Each post in our dataset is annotated from three different perspectives: the basic, commonly used 3-class classification (i.e., hate, offensive or normal), the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 32 publications
0
68
0
Order By: Relevance
“…Hate speech detection has branched into several sub-tasks like toxic span extraction [30,31], rationale identification [32] and hate target identification [20]. Though recent advancement in the field of NLP has pushed the limits of hate speech identification, like transformers [25] and graph neural networks [33,25,34] with people attempting to induce external knowledge leveraging author profiling [25] or ideology [35] but using context of the conversation is still a challenge with very little work exploring this problem.…”
Section: Related Workmentioning
confidence: 99%
“…Hate speech detection has branched into several sub-tasks like toxic span extraction [30,31], rationale identification [32] and hate target identification [20]. Though recent advancement in the field of NLP has pushed the limits of hate speech identification, like transformers [25] and graph neural networks [33,25,34] with people attempting to induce external knowledge leveraging author profiling [25] or ideology [35] but using context of the conversation is still a challenge with very little work exploring this problem.…”
Section: Related Workmentioning
confidence: 99%
“…The datasets selected for the study are the HateXplain [17], Social Bias Inference Corpus (SBIC) [21], and the Jigsaw 1 datasets. Our selection of these three datasets is founded on the basis that they address a similar problem (toxic text), yet they are diverse in how the annotations were collected.…”
Section: Datamentioning
confidence: 99%
“…To navigate the challenges with existing datasets, several studies have suggested alternative approaches to annotation tasks and model development. For example, Matthew et al [17] posit that training models by highlighting the portion of a particular text that people use to distinguish offensive text from normal text can improve model performance. Also, Sap et al [20] show that priming annotators before annotation tasks can reduce their insensitivity to different dialects and the occurrence of bias in ground-truth labels.…”
Section: Introductionmentioning
confidence: 99%
“…-Hate Speech: During the discussion of important events, some users can behave aggressively and even use hate speech towards other individuals or groups of people. We apply RoBERTa [23] fine-tuned for the task of detecting hate speech and offensive language [25] to the tweet contents. Text filtering and cleaning are applied as in sentiment analysis.…”
Section: Experimental Designmentioning
confidence: 99%